Effects of silica/carbon black hybrid filler on mechanical properties and mophology of styrene butadiene rubber-acrylonitrile butadient rubber blends - Jansamorn Ma-iat (Chulalongkorn University, 2013)
Thesis (M.Sc.)-- Chulalongkorn University, 2010